Micromechanical modeling of damage and load transfer in particulate composites with partially debonded interface. (1st November 2016) - Despringre, Nicolas; Chemisky, Yves; Bonnay, Kevin; Meraghni, Fodil
Highlights: An original two-step damage law for short fiber reinforced composite is proposed. A quadratic damage criterion is computed at the fiber/matrix interface. The load transfer is reduced according to a shear lag model based evolution law. Validation is made against experimental and numerical data from literature. The model is also assessed with FE analysis including cohesive elements at interface. Abstract: A new micromechanical damage model accounting for progressive interface debonding is developed for composite materials. It consists of an original evolution law of the damage at the interface and an appropriate load transfer law at the matrix-fiber interface integrated into a generalized incremental Mori–Tanaka homogenization scheme. The interface damage evolution is driven by the interfacial stress state while the load transfer is obtained from a new model inspired by the shear lag model. Specifically, such damage evolution is supported by experimental microscopic observations for short glass fiber reinforced polyamide-66. The proposed model is validated based on numerical reference solutions provided from finite element analyses of a representative unit cell of a composite, where imperfect interfaces are represented using cohesive elements. A further comparison with experimental data proves that the proposed model is an alternative to micromechanical models involving weak interfaces in the case of spherical reinforcements. It is shown that the proposed model is able to accurately reproduce the non-linear effective response of composite materials for a broad range of reinforcement shapes, including spherical particles and matrix mechanical properties.